PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DENGAN PERCEIVED VALUE SEBAGAI VARIABEL MODERATING - Makardiono Satata (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the impact of service quality on customer satisfaction on building Gedung Purna Yudha Surakarta. To analyze the significance of the effect of perceived value to customer satisfaction on building Gedung Purna Yudha Surakarta. To analyze the moderating effect of perceived value on the impact of service quality on customer satisfaction on building Gedung Purna Yudha Surakarta. In conclusion: There was a significant effect of service quality on customer satisfaction using the services of building Gedung Purna Yudha Surakarta. There was a significant effect of perceived value on customer satisfaction using the services of building Gedung Purna Yudha Surakarta. The test results concluded that the absolute difference in perceived value variable does not moderate the effect of variable quality of service to customer satisfaction using the services of on building Gedung Purna Yudha Surakarta. Keywords: Service Quality, Perceived Value, Customer Satisfaction.